Beam-Background Tests with TOTEM Roman Pot Detectors at the LHC Injection Energy - Jan Kašpar (Instruments, 2018)
With the aim of measuring the total cross-section and the ρ parameter, TOTEM has performed tests of beam conditions at the LHC injection energy of s = 900   GeV . The tests have revealed complications in setting up the LHC collimators to minimise the background observed in the Roman Pot (RP) detectors, summarised in this article. In two tests a subset of the RPs was exposed to background compatible with the physics requirements. If no improvement of the collimation strategy is found, it is shown that a small retraction of the RPs can significantly reduce the observed background level.